Strategi Komunikasi Kampung Wisata Purbayan dalam Meningkatkan Pelestarian Kebudayaan Kotagede - Wanda Ayu Warohmah; Olla Agustia Leriani; Mega Ardina (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study was conducted due to the importance of communication in helping to preserve culture amid the growth of community-based tourism and advances in digital technology that influence the way people communicate. Purbayan Tourism Village, as a cultural tourist destination in Kotagede, plays a vital role in conveying and preserving cultural heritage through various communication activities involving the community and relevant stakeholders. This study aims to understand how communication strategies influence efforts to preserve Kotagede’s culture. The study employs a quantitative approach using a survey method. Data were collected through a questionnaire administered to 102 respondents selected via purposive sampling. Data analysis was conducted using descriptive statistics, validity testing, reliability testing, and simple linear regression analysis using IBM SPSS Statistics software. The study found that all measurement instruments were valid and reliable, with a Cronbach’s Alpha value of 0.937 for the communication strategy variable and 0.923 for the cultural preservation variable. The results of the regression analysis showed a coefficient of 0.694 and a significance level of 0.000, indicating that communication strategies have a positive and highly significant impact on cultural preservation efforts. The communication strategies employed successfully increased public understanding and participation in preserving culture.